2019
DOI: 10.17159/2519-0105/2019/v74no5a6
|View full text |Cite
|
Sign up to set email alerts
|

Errors in root canal preparation: a review of the literature and clinical case reports

Abstract: Chemo-mechanical preparation and the removal of infected dentine in order to eliminate microorganisms and avoid apical periodontitis remain the main objectives in endodontic treatment. Mechanical preparation of the root canal system not only provides the space for obturation but also facilitates disinfection of the root canal system through the use of irrigation solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…The present study showed that all of the file systems had an improved TTF/NCF when FRM was employed, in accordance with the findings derived from V Faus-Matoses (2022) [29], Ferreira F et al (2017) [46], and Van der Vyver 2020 [47], who indicated that the resistance of NiTi alloy endodontic rotary files to cyclic fatigue was better when reciprocating motion was used compared to CR.…”
Section: Discussionsupporting
confidence: 91%
“…The present study showed that all of the file systems had an improved TTF/NCF when FRM was employed, in accordance with the findings derived from V Faus-Matoses (2022) [29], Ferreira F et al (2017) [46], and Van der Vyver 2020 [47], who indicated that the resistance of NiTi alloy endodontic rotary files to cyclic fatigue was better when reciprocating motion was used compared to CR.…”
Section: Discussionsupporting
confidence: 91%
“…Liquid growth/viability assays were performed either as stand-alone procedures or prior to anti-biofilm activity measurements (30 reports 9,50,57,58, ) and as a comparative method in one 86 of the four reports that investigated EOW effectiveness by agar diffusion assays. 66,[86][87][88] In vitro adherence and anti-biofilm assays (36 reports) were performed using laboratory biofilm models (11 reports, 70,[73][74][75][77][78][79][89][90][91][92] ), extracted human teeth (14 reports 90,91,[93][94][95][96][97][98][99][100][101][102][103][104] ), bovine teeth (1 report 105 ) and biomaterial substrates (10 reports 24,61,83,[106][107][108][109][110][111][112] ).…”
Section: Antimicrobial Efficacymentioning
confidence: 99%
“…Ledge formation typically occurs when rigid files with sharp, inflexible cutting tips are used in a rotational motion within a curved root canal. It can also result from the repeated application of pressure with the same file at a certain level, especially before the beginning of an apical curve, the use of nonprecurved stainless steel files, insufficient pre-flaring, or the absence of a glide path [11] (Fig. 2).…”
Section: Ledge Formationmentioning
confidence: 99%
“…The only chance to address this error is to introduce into the canal a fine K-file (08 to 010), very strongly precurved, with 1-2 mm apical slight movements and a 30° watch-winding rotation, which will inevitably deviate from the false trajectory [11,13].…”
Section: Complications During Root Canal Shapingmentioning
confidence: 99%